ANALISIS SIRKULASI PENUMPANG TERMINAL PENUMPANG KAPAL LAUT (TPKL) TANJUNG MAS SEMARANG (Program Studi Arsitektur, Fakultas Teknik dan Informatika, Universitas PGRI Semarang, 2022)
ABSTRACTThe Passengership Terminal is the main part of the sub Port system which serves to accommodate the activities of passenger transport processes from one sea transportation system to another. As a result of its function as the activity-area of the passenger transferal process, making the passenger terminal have many high circulation needs facilities. The activities what’s happen inside the terminal is mainly affected by people and stuff. The Passengership Terminal Port of Tanjung Mas Semarang were among the international terminals in central Java worked well service and accommodate various passenger activities. Discomport in activities, and uncertainly of the flow of grooves often arises as a result of unitended circulation pattern in Passengership Terminal. Planning a proper circulation in the Passenger Terminal requires studies of the element of circulation such as attainment, circulation pattern, circulation ways, and the circulation of space. Therefore, we have raised the topic for further consideration of the circulation of the Passengership Terminal Port of Tanjung Mas Semarang for margin. Keyword : Passenger Terminal, Tanjung Mas Semarang, Circulation